Universidade e educação ambiental - Chao, Cheg Hsin Nery (2005)
The society consists of the inter-relations between diverse symbolic fields of performance, where some agents if identify for values, habits and goals. The present thesis analyzed, taking for base the Theory of the Social Field of Pierre Bourdieu, the ambient field and the university, leaving of the principle that the university is one of the propitious places for the quarrel, study, knowledge elaboration, and that the ambient education is one of the ways of dissemination of knowledge and action in favor of the ambient question. It was looked to contextualize and to identify the main factors that configure the university while a social field, and to evidence the conflict and connector links with the ambientalism. It is perceived university as space of tensions, whose produced capital stock in the academic scope must be enough convincing in the direction of the social transformation, of the expansion of conscience, the critical matureness, and thus to appear as agent of social transformation. The joint between the diverse social fields, promoted for the university, will be able to contribute for knowledge formularization that can consist base for elaboration of politics and programs to answer to the problems of the society contemporary. It has the inter-relationship between the two fields, however, this relation still is fragile, needing that a continuity practical social that they make possible that the ambient question is part of the culture of the university. This will be able to give with the intensification of the actions and the inclusion of the ambient questions in the communication mechanisms and administrative management. To surpass discontinuities caused for changes of groups leading and for interests politician conjunctural are necessary that they create habitus, what passes for the institutionalization of practical and the constitution of a culture that the agents allow if to reorganize defending the interests of social transformation front to the economic interests, as much in the university how much in the ambient field